Republic of Latvia : Third Review Under the Stand-By Arrangement and Financing Assurances Review, Request for Rephasing of Purchases Under the Arrangement, and Request for Waiver of Applicability of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2010)
The labor market remains weak, disinflation has slowed, but falling wages are improving competitiveness. The weak economic environment is putting pressure on the banking sector. Financial conditions have deteriorated recently because of international financial market tensions. The Bank of Latvia has strengthened its liquidity management framework. Program implementation remains broadly on track. Strengthening the Ministry of Finance's control over fiscal decisions is crucial. The government needs to accelerate Mortgage and Land Bank's restructuring and facilitate market-based debt resolution. Program implementation to date has helped insulate Latvia from the recent international financial market turmoil.